Financial, economic and environmental analyses of upgrading reverse osmosis plant fed with treated wastewater - Foroogh Nazari Chamaki; Glenn P. Jenkins; Majid Hashemipour (Queen's University, Department of Economics, 2023)
One of the most effective strategies to mitigate water shortages worldwide is to reuse the treated wastewater for freshwater production employing reverse osmosis (RO) technology. This strategy is appropriate in urban areas of arid or semi-arid regions as it can provide a sustainable and reliable water source close to the consumers. One of the drawbacks of RO is the high variability of production costs due to the electricity intensity. In addition, depending on the electricity source, it can also result in substantial environmental costs. [...]
Keywords: I38; L95; H43; Q25; 330; circular economy; reused wastewater; reverse osmosis; levelized cost; economic cost; membrane technologies; emission cost; environmental externalities; distributive analysis; energy saving